2016
DOI: 10.1111/codi.13086
|View full text |Cite
|
Sign up to set email alerts
|

Intersphincteric completion proctectomy with omentoplasty for chronic presacral sinus after low anterior resection for rectal cancer

Abstract: Aim This study aimed to determine the clinical outcome of salvage surgery without restoring continuity for symptomatic chronic presacral sinus after low anterior resection (LAR) for rectal cancer.Method Out of a prospective cohort of 46 patients with chronic presacral sinus (> 1 year after LAR), 27 underwent completion proctectomy with omentoplasty between January 2005 and July 2014.Results The initial treatment for rectal cancer included neoadjuvant radiotherapy in 26 (96%) patients. Besides a chronic presacr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 17 publications
0
30
0
Order By: Relevance
“…The sinus might be asymptomatic, but can also be a source of major morbidity even up to life-threatening necrotising fasciitis of the upper leg [ 11 ]. Management of the chronic sinus means major surgery taking down the leaking anastomosis followed by either redo anastomosis or intersphincteric proctectomy with omentoplasty and permanent colostomy [ 12 ]. The Dutch TME trial showed that after secondary stoma formation for infectious problems, the deviating stoma could not be reversed in 49% with preoperative radiotherapy as an independent predictor (HR 0.34) [ 13 ].…”
mentioning
confidence: 99%
“…The sinus might be asymptomatic, but can also be a source of major morbidity even up to life-threatening necrotising fasciitis of the upper leg [ 11 ]. Management of the chronic sinus means major surgery taking down the leaking anastomosis followed by either redo anastomosis or intersphincteric proctectomy with omentoplasty and permanent colostomy [ 12 ]. The Dutch TME trial showed that after secondary stoma formation for infectious problems, the deviating stoma could not be reversed in 49% with preoperative radiotherapy as an independent predictor (HR 0.34) [ 13 ].…”
mentioning
confidence: 99%
“…This could explain the fact that despite sufficient length and volume, an OP was not superior to primary wound closure in this study. It therefore may be important to distinguish primary APR from a situation with a clear infectious problem located in the pelvis [13,14]. Intuitively, in those instances, OP would decrease the risk of recurrent abscess formation and small bowel fistula that can potentially occur when the small bowel descend into such an irradiated abscess cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Salvage surgery for pelvic septic complications following colorectal surgery most often dictates radical removal of pelvic bowel structures with a definitive ostomy [4]. Patients undergoing redo surgery are prone to develop recurrent infectious complications.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research suggests that obliterating the pelvic space with an omentoplasty after abdominoperineal resection for rectal cancer results in enhanced perineal wound healing and a decrease in sinus formation due to angiogenesis and enhancement of the inflammatory response [5]. Pelvic dead space obliteration after salvage surgery is also described for this purpose [4]. In the absence of omentum, and considering the morbidity associated with autologous tissue flaps, obliteration of pelvic dead space with viable mesentery of a bowel segment that has to be removed as part of salvage procedures seems to be a valuable alternative.…”
Section: Discussionmentioning
confidence: 99%